Random Transposon Mutagenesis of Campylobacter jejuni - Golden, Neal J. (American Society for Microbiology, 2000)
Genetic studies of Campylobacter jejuni have been limited due to the lack of a transposon mutagenesis method. Here, we describe a novel technique for random transposon mutagenesis using a mariner-based transposon into C. jejuni strain 480. Insertions were random, as demonstrated by Southern blot analysis and insertional junction sequencing. We have demonstrated, for the first time, random in vivo transposon mutagenesis of C. jejuni.